2001
DOI: 10.1038/sj.ijir.3900761
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the relationship between prostate size, peak urinary flow rate and male erectile dysfunction

Abstract: This study sought to identify whether a true relationship exists between benign prostatatic hyperplasia (BPH) and erectile dysfunction (ED). In a community-based study, 427 men underwent transrectal ultrasound (TRUS), uroflow studies and a questionnaire concerning erectile function. ED had a significant correlation to age (r ¼ 0.19, P < 0.001). But comparisons of prostate volume and analysis of maximum flow rate showed no significant difference between three erectile functional groups; ranging from no ED to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
2
20
1
1
Order By: Relevance
“…Overall, a strong relationship between LUTS and ED was found but there was no relationship between urine flow rate and ED. In another study, age was found to be the only variable that was significantly related to prostate volume, peak urinary flow rate, and ED but no relationship was found between these values [14]. However, the unpublished data of McVary et al, which were referred to in the study of Schiff et al, revealed a strong negative relationship between all five subscales of sexual function that were surveyed and both the AUA symptom score index and urine flow rate [15].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Overall, a strong relationship between LUTS and ED was found but there was no relationship between urine flow rate and ED. In another study, age was found to be the only variable that was significantly related to prostate volume, peak urinary flow rate, and ED but no relationship was found between these values [14]. However, the unpublished data of McVary et al, which were referred to in the study of Schiff et al, revealed a strong negative relationship between all five subscales of sexual function that were surveyed and both the AUA symptom score index and urine flow rate [15].…”
Section: Discussionmentioning
confidence: 91%
“…ED was classified into four categories: no ED (IIEF score 26-30), mild ED (IIEF score 17-25), moderate ED (IIEF score [11][12][13][14][15][16], and severe ED (IIEF score \11). Patients were classified into four age groups, separated by decades (50-59, 60-69, 70-79, and over 80).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, symptoms of LUTS and male sexual dysfunction were thought to be associated symptoms related to the aging process, but not causally linked [2,3]. More contemporary studies also can be found that contend that aging itself remains the primary link between LUTS and ED [27]. Throughout the past decade, evidence has been accumulating that shows a strong epidemiologic link between these two disease processes that is independent of age and other known risk factors for male sexual dysfunction.…”
Section: Epidemiologic Links Between Lower Urinary Tract Symptoms Andmentioning
confidence: 94%
“…Green et al [18] reported on a study of men between the ages of 55 and 70 years who were identified from patient lists from general practice clinics in the United Kingdom. Of the 4060 men invited, 2064 (50%) participated.…”
Section: Benign Prostatic Hyperplasia and Erectile Dysfunctionmentioning
confidence: 99%